Citation Dynamics and Impact of Articles in the Journal of Learning for Development: An Altmetric and Bibliometric Perspective - Mondal, Debdas (Information Research Communications, 2025)
Purpose This study aims to conduct a comprehensive bibliometric and altmetric analysis of research articles published in the Journal of Learning for Development to examine publication patterns, citation impact, thematic trends, and online attention. Design/Methodology/Approach Data were collected from the journal Web site, Google Scholar, and Altmetric.com, and analyzed using Microsoft® Excel, IBM Statistical Package for the Social Sciences, and VOSviewer. Bibliometric methods included citation analysis, keyword co-occurrence, and thematic mapping, while altmetric indicators were used to assess online engagement. Findings The study reveals that research output is globally distributed but concentrated in a few leading countries, with India contributing the highest number of publications. Citation analysis identifies influential articles on open learning, mobile learning, massive open online courses, Open Educational Resources policies, and digital inclusion. A strong positive correlation (r=0.62, p<0.01) between citation counts and Altmetric Attention Scores indicates that online engagement is a meaningful predictor of scholarly impact. Keyword frequency and co-occurrence analyses highlight thematic clusters centered on open educational resources, technology-enabled pedagogy, and information and communication technology. Twitter and X dominate online attention, while Mendeley readership indicates substantial scholarly interest. Originality This study provides novel insights into the intellectual structure, visibility, and evolving research priorities of Journal of Learning for Development, highlighting the interplay between traditional bibliometric measures and online attention metrics in the field of digital and open learning.
Keywords: Altmetrics; Bibliometrics; Citation analysis; Journal of Learning for Development (JLD); Keyword analysis; Mobile learning; Massive Open Online Courses (MOOCs); Open educational resources; Research impact.